(3JbdHGJ CSYGQ GdUQa (B/s - (3GdehShj, VjGA eLjOs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2016)
(3JfGhd gPG GdcJGH JbdHGJ CSYGQ GdUQa ef NdGd SHYI aUhd JMOK ajgG Yf JcGaD GdbhI GdTQGFjI ebGHd GdShb, deGPG CSYGQ UQa MbjbjI, Cj GdeYOdI HfSHI GdJVNe, hYf SYQ GdUQa hGdSjGSI GdfbOjI, hGdYedI GdehMOI dJLfH GdefGaSI aj CSYGQ GdUQa hCfXeJgG , hdeGPG GJLgJ GdOhd Gdi JHfj fXe UQa eQfI, hCNjQG UfOhb dfbO GdOhdj aj JMjO CSYGQ GdUQa(B.s
(3GdeQGLY U(B.112s
Keywords: (3CSYGQ GdUQas; (3GdHfhc (B- (3GdLRGFQs